Preparation of'logistics net '-imitated polyion liquid-metal organic framework composite material and application in carbon capture
By introducing the polyionic liquid-metal organic frame composite material PIL/ZIF-8, which is a "logistics network" in the mixed matrix membrane, the problem of poor compatibility between fillers and polymer matrix in the prior art is solved, and high efficiency is achieved The CO2 separation performance overcomes the "trade-off" effect.
Patent Information
- Application Number
- CN202411846849.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-11
AI Technical Summary
In the CO2 separation, the existing mixed matrix membrane has poor compatibility between fillers and polymer matrix, which leads to interface defects and affects gas separation performance. Moreover, ZIF-8 cannot form a continuous CO2 transmission path in MMMs, which is limited to improving separation performance.
A polyionic liquid-metal-organic framework composite material PIL/ZIF-8, which is a "logistics network", is designed to construct a fast CO2 transfer path in the mixed matrix membrane as a filler, and reduce interface defects through hydrogen bonding.
Effectively accelerate the selective transmission of CO2 in the mixed matrix membrane, improve CO2/CH4 selectivity and separation performance, overcome the "trade-off" effect, and achieve high permeability and high separation factors.
Smart Images

Figure HDA0005189447950000011 
Figure HDA0005189447950000012 
Figure HDA0005189447950000013
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of mixed matrix membrane material preparation, and in particular to the preparation of a polyionic liquid-metal organic framework composite material imitating a "logistics network" and its application in carbon capture. Background Art
[0002] The efficient capture of carbon dioxide in natural gas (mainly CH4) is an issue that needs to be urgently addressed. In order to remove impurity gases (CO2), it is very important to develop a simple and effective separation method. At present, the traditional separation methods include solvent absorption, pressure swing adsorption, and low-temperature separation. They have excellent separation performance, but have disadvantages such as high equipment investment, complex equipment operation, high energy consumption, and high pollution. In contrast, membrane separation technology has been widely recognized for its advantages such as simple operation, low energy consumption, and no pollution emissions. Therefore, membrane separation technology is expected to lead the green and environmentally friendly path of CO2 separation technology in the future.
[0003] Membrane materials are the core components of gas separation membranes. According to the different membrane materials, gas separation membranes can be divided into polymer membranes, inorganic membranes and mixed matrix membranes (MMMs). Polymer membranes have the advantages of low cost, good mechanical properties and easy operation, but their polymer membranes are often limited by the "trade-off" effect, making it impossible for them to have both high permeability and high selectivity. Inorganic membranes show better thermal and chemical stability than polymer membranes, but their structures are fragile and their processing performance is poor. Mixed matrix membranes are composed of continuous polymer matrices and fillers, combining the advantages of polymer membranes and inorganic membranes, while deriving the advantages of both high permeability and high selectivity, so they have the potential to overcome the "trade-off" effect. Mixed matrix membranes currently face the problem of poor compatibility between fillers and polymer matrices, which leads to the generation of interface defects, which will seriously affect gas separation performance.
[0004] Zeolitic imidazole framework-8 (ZIF-8) is one of the most representative metal organic frameworks (MOFs), which has a large specific surface area and abundant CO2-philic groups and sites, and has a strong affinity for CO2. However, ZIF-8 cannot form a continuous CO2 transfer path in MMMs, so the improvement of the CO2 separation performance of mixed matrix membranes by introducing ZIF-8 is limited. Therefore, it is necessary to design a filler to improve the CO2 separation performance of mixed matrix membranes. . Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a preparation of a polyionic liquid-metal organic framework composite material that imitates a "logistics network" and its application in carbon capture. The polyionic liquid-metal organic framework composite material PIL / ZIF-8 that imitates a "logistics network" prepared by the present invention is used as a filler to construct a fast CO2 transfer path in a mixed matrix membrane. The presence of its affinity group can generate hydrogen bonding with the high molecular polymer, thereby reducing the generation of interface defects and improving gas separation performance, and is used in CO2 capture. .
[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:
[0007] In a specific embodiment, the present invention provides a method for preparing a polyionic liquid-metal organic framework composite material that simulates a "logistics network", the method comprising the steps of:
[0008] (1) 1,4-bis(chloromethyl)benzene and 1-vinylimidazole are dissolved in acetonitrile, and the obtained solution is heated in a nitrogen atmosphere. After centrifugation, the solution is washed with acetonitrile and vacuum dried to obtain a monomer of a polyionic liquid [PMEI]Cl;
[0009] (2) Zn(NO3)2·6H2O is dispersed in methanol to obtain solution A, and 2-methylimidazole is dispersed in methanol to obtain solution B. The two solutions are then mixed and stirred under ultrasonic conditions, and the resulting solid is collected by centrifugation, washed with methanol, and vacuum dried to obtain ZIF-8.
[0010] (3) Dispersing the ZIF-8 prepared in step (2) in ethanol, adding the [PMEI]Cl and azobisisobutyronitrile prepared in step (1) to the above dispersion, heating and stirring in a nitrogen atmosphere, collecting the obtained solid by centrifugation, and washing with ethanol. Finally, drying the collected solid under vacuum conditions to obtain PIL / ZIF-8.
[0011] Furthermore, in step (1), the amount of 1,4-bis(chloromethyl)benzene, 1-vinylimidazole and acetonitrile is 0.5 g:0.6 g:20 mL; the heating temperature is 60-80° C., and the heating time is 12 h to 24 h.
[0012] In step (2), the concentration of solution A is 2.5-3 g / mL, and the concentration of solution B is 3-3.5 g / mL; the volume ratio of solution A to solution B is 100 mL:100 mL; and the stirring time is 12-24 h.
[0013] The concentration of ZIF-8 in step (3) is 4 mg / mL; the dosage of ZIF-8, [PMEI]Cl, and azobisisobutyronitrile is in the ratio of 0.2 g: 0.2-0.6 g: 0.04; the heating temperature is 70-90° C., and the heating time is 24 h.
[0014] In a specific embodiment, the present invention also provides a polyionic liquid-metal organic framework composite material that imitates a "logistics network" prepared by the above preparation method.
[0015] In a specific embodiment, the present invention also provides the application of the above-mentioned polyionic liquid-metal organic framework composite material imitating the "logistics network" in carbon capture.
[0016] In a specific embodiment, the present invention also provides a mixed matrix membrane, wherein the mixed matrix membrane uses PIL / ZIF-8 as a filler and sulfonated polyetheretherketone SPEEK as a base material, and the filler and the base material are physically blended at room temperature to form; the thickness of the mixed matrix membrane is 110 to 128 μm; the mass percentage of the filler in the mixed matrix membrane is 3% to 9%.
[0017] Furthermore, the present invention also provides the use of the mixed matrix membrane in CO2 capture.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The present invention provides a method for preparing a polyionic liquid-metal organic framework composite material that simulates a "logistics network", and uses the prepared PIL / ZIF-8 as a filler to physically blend with sulfonated polyetheretherketone SPEEK to form a mixed matrix membrane. The PIL and ZIF-8 in the PIL / ZIF-8 can respectively serve as a "logistics route" and a "logistics node" in the "logistics network", thereby effectively accelerating the selective transfer of CO2 in the mixed matrix membrane and improving the CO2 / CH4 selectivity and separation performance. An efficient CO2 transfer path is constructed in the mixed matrix membrane with sulfonated polyetheretherketone SPEEK as the matrix, thereby improving the permeability-selectivity performance of the mixed matrix membrane, overcoming the trade-off effect, and having a high permeability and a high separation factor.
[0020] The present invention overcomes the disadvantages of ZIF-8 filler and can combine the advantages of PIL and ZIF-8 filler to achieve synergistic effect; the preparation process of mixed matrix membrane is simple, the reaction is controllable, the raw materials are cheap and easy to obtain, and the conditions are mild, which can promote the complementary advantages of inorganic filler and polymer matrix. The research results show that the permeation selectivity of the present invention for CO2 / CH4 mixed gas has a maximum CO2 flux of 1641±42 Barrer and a CO2 / CH4 selectivity of 32±0.9. It exceeds the Robeson upper limit in 2008. It provides a new and effective strategy for the efficient separation of CO2. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the transmission electron microscopy image of PIL / ZIF-8;
[0022] Figure 2 is a scanning electron microscopy cross-sectional image of the prepared SPEEK / PIL / ZIF-8-3 mixed matrix membrane;
[0023] Figure 3 is a scanning electron microscopy cross-sectional image of the prepared SPEEK / PIL / ZIF-8-5 mixed matrix membrane;
[0024] Figure 4 is a scanning electron microscopy cross-sectional image of the prepared SPEEK / PIL / ZIF-8-7 mixed matrix membrane;
[0025] Figure 5 is a scanning electron microscopy cross-sectional image of the prepared SPEEK / PIL / ZIF-8-9 mixed matrix membrane;
[0026] Figure 6 This is a scanning electron microscope cross-sectional image of the prepared pure SPEEK membrane. DETAILED DESCRIPTION
[0027] The present invention will be further explained below. These examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Experimental methods without specific conditions in the examples are all based on conventional conditions. The reagents and materials used, unless otherwise specified, can be obtained from commercial channels.
[0028] Example 1
[0029] (1) 0.5 g of 1,4-bis(chloromethyl)benzene and 0.6 g of 1-vinylimidazole were dissolved in 20 mL of acetonitrile, and the resulting solution was heated at 80° C. for 24 h in a nitrogen atmosphere. After centrifugation, the mixture was washed with acetonitrile and vacuum dried to obtain a monomer of a polyionic liquid [PMEI]Cl;
[0030] (2) 2.975 g of Zn(NO3)2·6H2O was dispersed in 100 mL of methanol to obtain solution A, and 3.284 g of 2-methylimidazole was dispersed in 100 mL of methanol to obtain solution B. The two solutions were then mixed and stirred under ultrasonic conditions for 12 h, and the resulting solid was collected by centrifugation, washed with methanol, and vacuum dried to obtain ZIF-8.
[0031] (3) 0.2 g of ZIF-8 prepared in step (2) was dispersed in 50 mL of ethanol, and 0.4 g of [PMEI]Cl and 0.04 g of azobisisobutyronitrile prepared in step (1) were added to the above dispersion, heated and stirred at 80° C. in a nitrogen atmosphere for 24 h, and the obtained solid was collected by centrifugation and washed with ethanol. Finally, the collected solid was dried under vacuum conditions to obtain PIL / ZIF-8.
[0032] Figure 1 is the transmission electron microscopy image of PIL / ZIF-8; Figure 1 It can be seen that ZIF-8 particles can be connected into a network structure through PIL. PIL and ZIF-8 in PIL / ZIF-8 can act as "logistics routes" and "logistics nodes" in the "logistics network" respectively, thereby effectively accelerating the selective transfer of CO2 in the mixed matrix membrane and improving the CO2 / CH4 selectivity and separation performance. The constructed polyionic liquid-metal organic framework composite material PIL / ZIF-8 that mimics the "logistics network" can construct a fast CO2 transfer path in MMMs, which can synergistically improve the CO2 separation performance of the mixed matrix membrane.
[0033] Example 2
[0034] (1) 0.5 g of 1,4-bis(chloromethyl)benzene and 0.6 g of 1-vinylimidazole were dissolved in 20 mL of acetonitrile, and the resulting solution was heated at 70° C. for 24 h in a nitrogen atmosphere. After centrifugation, the mixture was washed with acetonitrile and vacuum dried to obtain the monomer [PMEI]Cl of the polyionic liquid;
[0035] (2) 3 g of Zn(NO3)2·6H2O was dispersed in 100 mL of methanol to obtain solution A, and 3.5 g of 2-methylimidazole was dispersed in 100 mL of methanol to obtain solution B. The two solutions were then mixed and stirred under ultrasonic conditions for 18 h, and the resulting solid was collected by centrifugation, washed with methanol, and vacuum dried to obtain ZIF-8.
[0036] (3) 0.2 g of ZIF-8 prepared in step (2) was dispersed in 50 mL of ethanol, and 0.6 g of [PMEI]Cl and 0.04 g of azobisisobutyronitrile prepared in step (1) were added to the above dispersion, heated and stirred at 80° C. in a nitrogen atmosphere for 24 h, and the obtained solid was collected by centrifugation and washed with ethanol. Finally, the collected solid was dried under vacuum conditions to obtain PIL / ZIF-8.
[0037] Example 3
[0038] 0.6g of SPEEK was weighed and dissolved in 10mL of N,N-dimethylacetamide solution, and stirred at 500r / min for 12h at room temperature to dissolve all the SPEEK particles to prepare a SPEEK matrix solution. 0.0186g of PIL / ZIF-8 prepared in Example 1 was physically blended with the SPEEK matrix solution, and stirred at room temperature for 12h to obtain a casting solution, which was poured onto a clean culture dish for casting; vacuum dried at 60°C for 24h, and then vacuum dried at 80°C for 24h to remove the residual solvent on the surface of the mixed matrix membrane to obtain a SPEEK / PIL / ZIF mixed matrix membrane, the thickness of which was 113μm. The weight percentage of PIL / ZIF-8 in the SPEEK / PIL / ZIF-8 mixed matrix membrane was 3%, so it was named SPEEK / PIL / ZIF-8-3 mixed matrix membrane.
[0039] Figure 2 is a scanning electron microscope cross-sectional image of the prepared SPEEK / PIL / ZIF-8-3 mixed matrix membrane. Figure 2 It can be seen that after the introduction of PIL / ZIF-8 into the SPEEK matrix, the cross-section of the mixed matrix membrane becomes rough, which proves the introduction of the filler. In addition, PIL / ZIF-8 is evenly distributed in the mixed matrix membrane without agglomeration.
[0040] Application of SPEEK / PIL / ZIF-8-3 mixed matrix membrane in CO2 capture at 30℃ and 2bar. A mixed gas of 80vol% CH4 and 20vol% CO2 was used as the feed gas. The dried membrane was moistened with deionized water and placed in a membrane tank for permeability testing. A circular stainless steel tank was placed in the oven to study the membrane (12.56cm 2, central part). In order to test the gas permeability of MMMs under different loads, the feed gas was introduced upstream of the membrane, the flow rate was controlled to be 50mL / min, and the pressure range was 0.2-0.8MPa. In addition, the permeabilities of CO2 and CH4 were calculated based on the sweep gas flow rate and its composition. The effects of H2 back diffusion and concentration polarization on data analysis can be ignored because the volume of the feed gas is much larger than the sweep gas (H2), and the back diffusion of H2 cannot change the composition of the feed gas. Therefore, H2 is suitable as the sweep gas on the downstream side of the membrane, and the flow rate is controlled at 30ml / min. A gas chromatograph (GC 2014C) was used to determine the content of each component in the permeate phase gas. The test results show that its CO2 flux is 1052±34Barrer (1Barrer=10 -10 cm 3 cm / cm 2 s cmHg), CO2 / CH4 selectivity is 26.7±0.8.
[0041] Example 4
[0042] In this embodiment, 0.0316g of PIL / ZIF-8 prepared in Example 1 was physically blended with a SPEEK matrix solution, stirred at room temperature for 12 hours to obtain a casting solution, and the casting solution was poured on a clean culture dish for casting; vacuum dried at 60°C for 24 hours, and then vacuum dried at 80°C for 24 hours to remove the residual solvent on the surface of the mixed matrix membrane, to obtain a SPEEK / PIL / ZIF-8 mixed matrix membrane, the thickness of which was 115μm. The weight percentage of PIL / ZIF-8 in the SPEEK / PIL / ZIF-8 mixed matrix membrane was 5%, so it was named SPEEK / PIL / ZIF-8-5 mixed matrix membrane.
[0043] Figure 3 is a scanning electron microscope cross-sectional view of the prepared SPEEK / PIL / ZIF-8-5 mixed matrix membrane. Figure 3 It can be seen that after PIL / ZIF-8 is introduced into the SPEEK matrix, the cross-section of the mixed matrix membrane becomes rough, which proves the introduction of the filler. Moreover, PIL / ZIF-8 is evenly distributed in the mixed matrix membrane without agglomeration. At 30°C and 2 bar, the prepared SPEEK / PIL / ZIF-8-5 mixed matrix membrane is used for the separation test of CO2 / CH4 mixed gas with a CO2 volume fraction of 20%. The test process is the same as that of Example 3. The CO2 flux is tested to be 1320±39 Barrer and the CO2 / CH4 selectivity is 29.7±1.
[0044] Example 5
[0045] In this example, 0.0452 g of the PIL / ZIF-8 prepared in Example 1 was physically blended with a SPEEK matrix solution, stirred at room temperature for 12 hours to obtain a casting solution, and the casting solution was poured onto a clean culture dish for casting; vacuum dried at 60°C for 24 hours, and then vacuum dried at 80°C for 24 hours to remove the residual solvent on the surface of the mixed matrix membrane, to obtain a SPEEK / PIL / ZIF-8 mixed matrix membrane, the thickness of which was 121 μm. The weight percentage of PIL / ZIF-8 in the SPEEK / PIL / ZIF-8 mixed matrix membrane was 7%, so it was named SPEEK / PIL / ZIF-8-7 mixed matrix membrane.
[0046] Figure 4 is a scanning electron microscope cross-sectional view of the prepared SPEEK / PIL / ZIF-8-5 mixed matrix membrane. Figure 4 It can be seen that after PIL / ZIF-8 is introduced into the SPEEK matrix, the cross-section of the mixed matrix membrane becomes rough, which proves the introduction of the filler. Moreover, PIL / ZIF-8 is evenly distributed in the mixed matrix membrane without agglomeration. At 30°C and 2 bar, the prepared SPEEK / PIL / ZIF-8-7 mixed matrix membrane is used for the separation test of CO2 / CH4 mixed gas with a CO2 volume fraction of 20%. The test process is the same as that of Example 3. After testing, its CO2 flux is 1641±41 Barrer, and the CO2 / CH4 selectivity is 32±0.9, and the gas separation performance is greatly improved.
[0047] Example 6
[0048] In this example, 0.0593 g of the PIL / ZIF-8 prepared in Example 1 was physically blended with a SPEEK matrix solution, stirred at room temperature for 12 hours to obtain a casting solution, and the casting solution was poured onto a clean culture dish for casting; vacuum dried at 60°C for 24 hours, and then vacuum dried at 80°C for 24 hours to remove the residual solvent on the surface of the mixed matrix membrane, to obtain a SPEEK / PIL / ZIF-8 mixed matrix membrane, the thickness of which was 128 μm. The weight percentage of PIL / ZIF-8 in the SPEEK / PIL / ZIF-8 mixed matrix membrane was 9%, so it was named SPEEK / PIL / ZIF-8-9 mixed matrix membrane.
[0049] Figure 5 is a scanning electron microscope cross-sectional view of the prepared SPEEK / PIL / ZIF-8-9 mixed matrix membrane. Figure 5It can be seen that after PIL / ZIF-8 is introduced into the SPEEK matrix, the cross-section of the mixed matrix membrane becomes rough, which proves the introduction of the filler. Moreover, the filling amount of PIL / ZIF-8 is too high, resulting in uneven distribution of PIL / ZIF-8 in the mixed matrix membrane and agglomeration. At 30°C and 2 bar, the prepared SPEEK / PIL / ZIF-8-9 mixed matrix membrane was used for the separation test of CO2 / CH4 mixed gas with a CO2 volume fraction of 20%. Its CO2 flux was 1330±35Barrer and CO2 / CH4 selectivity was 30.5±0.8.
[0050] Comparative Example 1
[0051] For comparison, 0.6 g of SPEEK was weighed and dissolved in 10 mL of N,N-dimethylacetamide solution, and stirred at 500 r / min for 12 h at room temperature to dissolve all the SPEEK particles. The resulting casting solution was poured onto a clean ultra-flat surface dish and cast, and vacuum dried at 60°C for 24 h, and then vacuum dried at 80°C for 24 h to remove the residual solvent on the surface of the mixed matrix membrane, thereby obtaining a SPEEK membrane with a thickness of 110 μm.
[0052] Figure 6 The figure is a scanning electron microscope cross-sectional image of the prepared pure SPEEK membrane. Figure 6 It can be seen that the cross section of the pure SPEEK membrane shows the typical morphology of a smooth, dense and defect-free polymer membrane. At 30°C and 2 bar, the SPEEK membrane was used for the separation test of a CO2 / CH4 mixed gas with a CO2 volume fraction of 20%. The CO2 flux was tested to be 720±32 Barrer and the CO2 / CH4 selectivity was 24±0.7.
[0053] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a polyionic liquid-metal organic framework composite material imitating a "logistics network", characterized in that: The preparation method comprises the steps of: (1) 1,4-bis(chloromethyl)benzene and 1-vinylimidazole are dissolved in acetonitrile, and the obtained solution is heated in a nitrogen atmosphere. After centrifugation, the solution is washed with acetonitrile and vacuum dried to obtain a monomer of a polyionic liquid [PMEI]Cl; (2) Zn(NO3)2·6H2O is dispersed in methanol to obtain solution A, and 2-methylimidazole is dispersed in methanol to obtain solution B. The two solutions are then mixed and stirred under ultrasonic conditions, and the resulting solid is collected by centrifugation, washed with methanol, and vacuum dried to obtain ZIF-8. (3) Dispersing the ZIF-8 prepared in step (2) in ethanol, adding the [PMEI]Cl and azobisisobutyronitrile prepared in step (1) to the above dispersion, heating and stirring in a nitrogen atmosphere, collecting the obtained solid by centrifugation, and washing with ethanol. Finally, drying the collected solid under vacuum conditions to obtain PIL / ZIF-8.
2. The preparation method according to claim 1, characterized in that: (1) The amount of 1,4-bis(chloromethyl)benzene, 1-vinylimidazole and acetonitrile used in step (1) is 0.5 g:0.6 g:20 mL; the heating temperature is 60-80° C. and the heating time is 12 h to 24 h. (2) In step (2), the concentration of solution A is 2.5 to 3 g / mL, and the concentration of solution B is 3 to 3.5 g / mL; the volume ratio of solution A to solution B is 100 mL:100 mL; and the stirring time is 12 to 24 h. (3) The concentration of ZIF-8 in step (3) is 4 mg / mL; the dosage of ZIF-8, [PMEI]Cl, and azobisisobutyronitrile is in the ratio of 0.2 g: 0.2-0.6 g: 0.04; the heating temperature is 70-90° C., and the heating time is 24 h.
3. Application of the polyionic liquid-metal organic framework composite material imitating the "logistics network" according to claim 1 in carbon capture.
4. A mixed matrix membrane, wherein the mixed matrix membrane uses a polyionic liquid-metal organic framework composite material that imitates a "logistics network" as a filler and a sulfonated polyetheretherketone SPEEK as a base material, and the filler and the base material are physically blended at room temperature to form the membrane; the thickness of the mixed matrix membrane is 110 to 128 μm; the mass percentage of the filler in the mixed matrix membrane is 3% to 9%.
5. Use of the mixed matrix membrane according to claim 4 in CO2 capture.